(untitled) (UNED Research Journal, 2020)
Introduction: The pocket gopher (Heterogeomys underwoodi) is harmful for agriculture but there is little information about its effect. Objective: To know about the impact of the pocket gopher Heterogeomys underwoodi to crops, characteristics of the mounds, as well as control techniques used by producers. Methods: We conducted a survey to 33 producers to determine damage and made a characterization of the mounds that this species builds. Results: A total of 34 crops suffer damage ranging from 25% to 50% loss. The damage occurs in dry and rainy seasons, and in different phenological stages (harvest time) depending on the crop. The most used combat techniques are toxic products, followed by traps, as well as the introduction of plants or animals into tunnel systems. Conclusion: these animals affect at least 34 crops and producers use a variety of control techniques.